Oriental Fish is one of the pottential fisheries commodity, which is contribute devisas for the country. Palmas Omatipinis is one of the new introduction arlifidal fish in Indonesia. Thats why we should know the feasibility analysis as a plan to develop in Oannaga Fish Culture. The study shows that fanning of Palmas Omatipinis in the beginning level process at Darmaga Fish Culture, feasible to be develop in tenn of maril.et aspect, technique aspect, managerial aspect and finansial aspect. The re - Iis Diatin; M Prihatna Sobari; Adiriani Sri Dharmasati (Buletin Ekonomi Perikanan, 2007)
Oriental Fish is one of the pottential fisheries commodity, which is contribute devisas for the country. Palmas Omatipinis is one of the new introduction arlifidal fish in Indonesia. Thats why we should know the feasibility analysis as a plan to develop in Oannaga Fish Culture. The study shows that fanning of Palmas Omatipinis in the beginning level process at Darmaga Fish Culture, feasible to be develop in tenn of maril.et aspect, technique aspect, managerial aspect and finansial aspect. The result given by discount rates 4 % I periode for scenario 1, shows the NPV is Rp 39.448.333.58, Net BlC is 1,23, and IRR is 5,45 %. For scenario 2, NPV is Rp 40.783.n5,19 , Net B/C is 1,24 and IRR is 5,54 %. The sensitivity analysis for scenario 1 shows that the business is not feasible if the price decrease to 20,7 % and hatcing rate decrease to 6,3 %. For scenario 2 business is not feasible if the price decrease to 21,3 % and hatcing rate decrease to 6,4 %